ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KORAN DI MASA KEMAJUAN TEKNOLOGI SEMAKIN MENINGKAT PADA PT ARISMA INDONESIA MERDEKA DI KABUPATEN OGAN KOMERING ULU - Malini, Hema; Tohir, Safaruddin; Mahendra, Oka (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2022)
This study is entitled Analysis of Factors Affecting Newspaper Purchasing Decisions in Times of Increasing Technological Progress at Pt Arisma Indonesia Merdeka in Ogan Komering Ulu Regency. This study aims to analyze the effect of consumer confidence, distribution and brand image on newspaper purchasing decisions at PT Arisma Indonesia Merdeka in Ogan Komering Ulu Regency. This research is descriptive and uses accidental sampling with a sample size of 94 respondents. Using multiple regression analysis techniques and to test the research hypothesis used the f test and t test. The results of the study are with multiple linear regression Y = 0.891 + 0.421X1 + 0.236X2 + 0.300X3. The equation can be interpreted that the constant is 0.891, which means that if consumer trust (X1), distribution (X2), and brand image (X3), the value is zero (not done), the purchase decision (Y) is 0.891. The coefficient value of purchasing decisions (X1) is 0.421, meaning that if consumer confidence (X1) increases by 1 unit, purchasing decisions (Y) will increase by 0.421. The distribution coefficient value (X2) is 0.236, meaning that if the distribution (X2) increases by 1 unit, the purchasing decision (Y) increases by 0.236. The brand image coefficient value (X3) is 0.300, meaning that if the brand image (X3) increases by 1 unit, the purchasing decision (Y) increases by 0.300. Determination testing obtained the contribution of consumer trust variables (X1), distribution (X2) and brand image (X3) to purchasing decisions (Y) of 80.9% while the remaining 19.1% was influenced or varied by other variables not included in this research model.